Impact of different ground-based microgravity models on human sensorimotor system - Saveko, Alina; Bekreneva, Maria; Ponomarev, Ivan; Zelenskaya, Inna; Riabova, Alexandra; Shigueva, Tatiana; Kitov, Vladimir; Abu Sheli, Nelly; Nosikova, Inna; Rukavishnikov, Ilya; Sayenko, Dimitry; Tomilovskaya, Elena (Frontiers in Physiology, 2023)
This review includes current and updated information about various ground-based microgravity models and their impact on the human sensorimotor system. All known models of microgravity are imperfect in a simulation of the physiological effects of microgravity but have their advantages and disadvantages. This review points out that understanding the role of gravity in motion control requires consideration of data from different environments and in various contexts. The compiled information can be helpful to researchers to effectively plan experiments using ground-based models of the effects of space flight, depending on the problem posed.